Novel FH mutation associated with multiple uterine leiomyomas in Chinese siblings - Zhao, Zichen (Mol Genet Genomic Med, 2019)
BACKGROUND: Fumarate hydratase (FH) plays an important role in cell metabolism. Germline mutation of FH may cause hereditary leiomyomatosis and renal cell cancer syndrome. The correlation between various mutations of FH gene and the phenotype is controversial and needs further study. Therefore, this article described a novel mutation in siblings with multiple uterine leiomyomas. METHODS: Whole‐exome sequencing was performed on the two patients and their family members using their peripheral blood. The function of the DNA variant was predicted in silico. RESULTS: Pathology results showed characteristics of leiomyoma. A novel missense mutation of FH gene (c.1214A＞G, p.Leu405Ser) was identified in both patients and their father. This mutation was predicted to be probably pathogenic and deleterious. CONCLUSION: This study indicated that the novel mutation may be responsible for the occurrence of multiple uterine leiomyomas. However, the risk of renal disease should not be ignored and regular screening was recommended.